Analytical solution for limit load of orthotropic pressure pipe with internal circumferential crack. (December 2018) - Yu, Qin; Zhou, Chang-Yu; Wang, Zi-Wen; He, Xiao-Hua
Highlights: The analytical solution for limit load of orthotropic pressure pipe with constant-depth internal circumferential crack under combined pressure, axial force and bending has been obtained. It is necessary to consider three directional stress for limit load of thick-walled pressure pipe with internal circumferential crack. The limit load of pipe under pure bending is only related to axial yield strength. The limit load of pipe under pure internal pressure is mainly determined by circumferential yield strength. Abstract: Based on the Hill yield criterion, considering three directional stress (r, θ, z ) of pressure pipe, the analytical solution for limit load of orthotropic pressure pipe with constant-depth internal circumferential crack under combined pressure, axial force and bending has been derived. The effect of crack size, anisotropy of pipe material, load (pressure, moment), and pipe size on the limit load of orthotropic pressure pipe is discussed. The results show that it is necessary to consider three directional stress for thick-walled pipe, and the influence of radial stress on the limit load cannot be ignored for thick-walled pipe. The limit load of pipe with constant-depth internal circumferential crack decreases with crack size. The limit load of pipe under pure bending is only related to axial yield strength. The limit load of pipe under pure internal pressure is mainly determined by circumferential yield strength. Graphical abstract: Image, graphical abstract